2015
DOI: 10.1155/2015/326493
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Loading Reflects Ulceration Risks of Diabetic Foot with Toe Deformation

Abstract: Diabetes has been one of the most common chronic diseases all over the world. The purpose of this study was to quantitatively assess the foot loading characteristics of diabetic patients with fifth-toe deformity through a comparative analysis with diabetic patients with healthy and normal feet. Six neuropathic diabetic female subjects with the fifth-toe deformation and six age-matched neuropathic diabetic controls without any feet deformities participated in the walking test. Dynamic barefoot plantar pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The CoP progression is a path formed by a series of coordinates passing from the hindfoot through to the forefoot during the stance phase [ 47 ]. CoP trajectory time progress in the medial forefoot region is near terminal stance (60% to 90%) of walking stance time [ 48 ]. The giant CoP medial–lateral displacement is believed to be an adaptation strategy and the redistributed plantar pressure [ 49 , 50 ], especially to the medial forefoot regions [ 49 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CoP progression is a path formed by a series of coordinates passing from the hindfoot through to the forefoot during the stance phase [ 47 ]. CoP trajectory time progress in the medial forefoot region is near terminal stance (60% to 90%) of walking stance time [ 48 ]. The giant CoP medial–lateral displacement is believed to be an adaptation strategy and the redistributed plantar pressure [ 49 , 50 ], especially to the medial forefoot regions [ 49 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calibration was conducted according to the manufacturer instructions before each trial. Pedar sensors of the appropriate size were inserted into the shoes and placed on the top of the insoles, after which the participants underwent a biomechanical plantar pressure analysis in five conditions (i.e., barefoot, and using the four different insoles) on a straight 10 m walkway with self-selected walking speed to perform their normal gait characteristic 8 , their average walking speed was 6.1 ± 1.2 m/s. For barefoot condition, the proper size Pedar sensors were attached with plantar and fixed by sock wearing without shoes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, foot types (mainly, normal, planus, and cavus feet) ( Buldt et al, 2015a ), foot posture (mainly, normal, pronated, and supinated feet) ( Hollander et al, 2019 ), toe morphology ( Mei et al, 2015a ), hallux valgus ( Hannah et al, 2016 ), and manipulated forefoot shapes (abducted hallux versus adducted hallux) ( Mei et al, 2016 ; Xiang et al, 2020a ; Xiang et al, 2020b ) have been previously reported in the literature. Pathological conditions, such as diabetic-related foot deformities ( Guiotto et al, 2013 ; Lu et al, 2015 ) can also influence the biomechanics. Figure 1 outlines the most common popular shape metrics ( Figure 1 ) and postures in the foot ( Figure 1 and Figure 2 ) with highlighted regions of variations in pronation (blue) and supination (red) when compared to those of the neutral foot posture.…”
Section: Foot Morphology Shape and Posture In Running Activitiesmentioning
confidence: 99%
“…Computational modeling of the foot ( Morales-Orcajo et al, 2016 ) revealed a higher concentrated von Mises stress at the metatarsals and higher contact pressure in the first metatarsophalangeal joint ( Zhang et al, 2018c ). Furthermore, the diabetic foot presented toe deformation with focalized pressure at the hallux ( Lu et al, 2015 ). Habitually, barefoot populations with increased hallux spacing have been associated with active gripping function ( Lambrinudi, 1932 ; Wallden, 2016 ), which expands the supporting area in the forefoot ( Mei et al, 2015a ; Mei et al, 2015b ; Shu et al, 2015 ; Wang et al, 2016 ) and higher medial longitudinal arch in the barefoot children’s cohorts ( Hollander et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%